A Survey of Crimean-Congo Hemorrhagic Fever Virus in Ticks of Shahr-e Ray, Iran, 2016-2017 - Pedram Talaie; Mohammad Mehdi Sedaghat; Ehsan Mostafavi; Zakiyeh Telmadarraiy; Mehdi Rouhani; Mostafa Salehi-Vaziri (Pasteur Institute of Iran, 2020)
Introduction: Crimean-Congo hemorrhagic fever (CCHF) is a tick-borne viral zoonosis with a considerable fatality rate. The virus is mainly transmitted to humans and animals through the bites of infected hard ticks belonging to the genus Hyalomma. This study aimed to determine the prevalence of CCHFV in ticks in Shahr-e Ray city, one of the meat supplier counties in Tehran Province, Iran. Methods: A molecular survey was carried out on collected ticks from sheep in slaughterhouses and husbandries of Shahr-e Ray city, during 2016-17. The ticks were identified using taxonomic characteristics, and the presence of CCHF virus RNA was investigated using an RT-PCR amplifying a 536 bp of the small segment of the viral genome. Results: The results of this study showed that the Hyalomma ticks were the dominant species in Shahr-e Ray slaughterhouses and husbandries. In none of the assayed ticks, RT-PCR detected CCHFV RNA. Conclusion: A considerable tick infestation with members of genus Hyalomma, among sheep in Shahr-e Ray slaughterhouses and husbandries, indicates the vulnerability of this county of tick-borne infections outbreaks such as CCHF. Therefore, applying acaricides and other preventive strategies should be adopted to control the tick population in Shahr-e Ray.